Molecular mechanisms of transcriptional control by Rev‐erbα: An energetic foundation for reconciling structure and binding with biological function. (11th June 2015) - Vaissière, Anaïs; Berger, Sylvie; Harrus, Deborah; Dacquet, Catherine; Le Maire, Albane; Boutin, Jean A.; Ferry, Gilles; Royer, Catherine A.
Abstract: Rev‐erbα and β are nuclear receptors that function as transcriptional repressors of genes involved in regulating circadian rhythms, glucose, and cholesterol metabolism and the inflammatory response. Given these key functions, Rev‐erbs are important drug targets for treatment of a number of human pathologies, including cancer, heart disease, and type II diabetes. Transcriptional repression by the Rev‐erbs involves direct competition with transcriptional activators for target sites, but also recruitment by the Rev‐erbs of the NCoR corepressor protein. Interestingly, Rev‐erbs do not appear to interact functionally with a very similar corepressor, Smrt. Transcriptional repression by Rev‐erbs is thought to occur in response to the binding of heme, although structural, and ligand binding studies in vitro show that heme and corepressor binding are antagonistic. We carried out systematic studies of the ligand and corepressor interactions to address the molecular basis for corepressor specificity and the energetic consequences of ligand binding using a variety of biophysical approaches. Highly quantitative fluorescence anisotropy assays in competition mode revealed that the Rev‐erb specificity for the NCoR corepressor lies in the first two residues of the β ‐strand in Interaction Domain 1 of NCoR. Our studies confirmed and quantitated the strong antagonism of heme and corepressor binding and significant stabilization of the corepressor complex by a synthetic ligand in vitro . We propose a model which reconciles the contradictory observations concerning the effects of heme binding in vitro and in live cells.